Problems that facing the philosophy of education in the variables of knowledge and Informatics society (techno _ social). (Journal Of Educational and Psychological Researches, 2012)
This research includes problems that facing the philosophy of education in the variables of knowledge and Informatics society (techno _ social). The problematic research included three questions: 1- What are the concepts and characterization related to the problematic of relationship between the philosophy of education and informatics variables (techno - social).2-What kind of problems facing speech philosophy of education in the variables information (techno - social)  3 - What are the perceptions of educational proposed to address problematic philosophy of education in the scope of human (human nature) and (values ​​and morals), in addition the research may explain the concepts and terms related to the subject and address nature methodology research and outlines, search has provided its answers to these questions through educational and philosophical and cultural resources, Which dealt with research topics regarding human problematic (human nature) and values ​​and morals problematic), and display concepts and describing such concepts (philosophy of education and knowledge society, information and techno - social and other concepts related to the research.Research was presented three chapters:- First chapter dealt Show concepts of research and characterization -The second chapter included two studies, First research addressing fields educational philosophizing and most important field is human, values ​​and morals, and the second research includes major changes and their relationship with problematic philosophy of education (human, human nature) (values ​​and morals) and these transformations are postmodernism, globalization, blowouts cognitive and informational and knowledge society, era digital (techno - social).The third chapter deals with the educational perceptions proposed to Arab education to Accommodate variables knowledge and information (techno - social) in the scope of human (human nature) and (values ​​and morals) and educational optimal for humans, values and morals in the future